Reuse of pacemakers, defibrillators and cardiac resynchronisation devices. Issue 1 (23rd January 2017) - Selvaraj, Raja J; Sakthivel, R; Satheesh, Santhosh; Ananthakrishna Pillai, Ajith; Sagnol, Pascal; Jouven, Xavier; Dodinot, Bernard; Balachander, Jayaraman
Abstract : Objective: Access to pacemakers remains poor among many patients in low/middle-income countries. Reuse of explanted pacemakers is a possible solution, but is still not widespread because of concerns regarding outcomes, especially infection. Our objective was to study early outcomes with implants using reused devices and compare them with those with implants using new devices. Methods: We studied all patients who underwent implantation of a new or reused pacemaker, cardiac resynchronisation therapy (CRT) device or implantable cardioverter defibrillator (ICD) in the last 5 years at a single institution. We analysed outcomes related to infection, device malfunction and device-related death within 6 months after initial implantation. Results: During the study period, 887 patients underwent device implant, including 127 CRT devices or ICDs. Of these, 260 devices (29.3%) were reused and the others were new. At 6 months, there were three device-related infections in implants using a new device. There were no infections among patients receiving a reused device. There were no device malfunctions or device-related deaths in either group. Conclusions: We found no difference in rate of infection or device malfunction among patients getting a reused device as compared with those with a new device. This study reinforces the safety of reusing devices for implant including CRT and ICDs.